Management Information Systems: Bibliometric Analysis and Its Effect on Decision Making - Budi Santoso; Try Hikmawan; Nani Imaniyati (Indonesian Journal of Science and Technology, 2022)
Decision-making in the organization always relates to the description of the results of the decisions taken. Therefore, every organization needs a management information system to assist in making various kinds of decisions needed. The purpose of this study was to determine the influence and effectiveness of management information systems on decision-making in the field of archives. The method used in this study is the explanatory survey method. Data collection techniques were carried out using questionnaires and product correlation moments. Data analysis was performed using simple regression analysis and hypothesis testing. The subjects of this study were 120 administrative employees in the city of Bandung. To support the analysis, this study also carried out a bibliometric analysis to determine trends in research development from information management systems to decision-making. Based on the findings, the quality of the management information system used is in the high category, as well as the effectiveness of decision-making is in the high category. Based on the results of hypothesis testing and significance, it can be interpreted that the management information system has a positive and significant effect on decision-making in the field of administration.